1996
DOI: 10.3382/ps.0750648
|View full text |Cite
|
Sign up to set email alerts
|

Effects of an In Ovo Injection of an Anti-Androgen on Embryonic and Posthatching Growth of Broiler Chicks

Abstract: Experiments were conducted to determine whether in ovo injection of Flutamide, a non-steroidal anti-androgen, would affect posthatching growth of broiler chickens. Before doing these studies it was necessary to develop a bioassay to demonstrate that Flutamide had anti-androgenic actions when injected in ovo. In ovo injection of 0.06 to 1.74 mumol of testosterone propionate (TP) per egg on the 8th d of incubation caused a dose-related decrease in weight of the bursa of Fabricius of newly hatched chicks. In subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
12
0
5
Order By: Relevance
“…study using the antiandrogenic chemical flutamide. (26) Although the histology from this study showed obvious differences in the appearance of the crosssections of the DDE-treated and control bursas, finding measurements to quantify these differences was challenging. Since B cells mature in the follicles, we assumed that disruption in the development of these structures would impact B cell maturation.…”
Section: Discussionmentioning
confidence: 97%
“…study using the antiandrogenic chemical flutamide. (26) Although the histology from this study showed obvious differences in the appearance of the crosssections of the DDE-treated and control bursas, finding measurements to quantify these differences was challenging. Since B cells mature in the follicles, we assumed that disruption in the development of these structures would impact B cell maturation.…”
Section: Discussionmentioning
confidence: 97%
“…In £utamide-treated clutches, ¢rst-laid eggs were injected controls and last-laid eggs were injected with £uta-mide, an anti-androgenic compound that blocks androgen receptor activation, in vehicle. The dose used (0.08 m mol) has anti-androgenic e¡ects on the development of the domestic fowl (Burke 1996). Injections were made on the day each egg was laid using the same procedure as described above for the collection of yolk samples.…”
Section: (C) Experimental Manipulation Of Yolk Testosteronementioning
confidence: 99%
“…Maternal androgens markedly affect offspring behaviour after hatching-they enhance offspring begging (Schwabl 1996;Eising & Groothuis 2003) and increase or reduce offspring growth and survival (Sockman & Schwabl 2000;Eising et al 2001;Eising & Groothuis 2003). Sex-specific effects of yolk androgens have hardly been studied, but they differentially affected sons and daughters in some studies (Burke 1996;Henry & Burke 1999) and not in others (Lipar & Ketterson 2000).…”
Section: Introductionmentioning
confidence: 99%